An assessment of the experiences of patients on the comprehensive HIV and AIDS care management and treatment programme in Tshwane, Gauteng - Magoro, Mmbangiseni Terrance (University of Limpopo (Medunsa Campus), 2009)
Background In order to provide an assessment of experiences of patients on the Comprehensive HIV and AIDS Care Management and Treatment (CCMT) programme it is essential to ascertain how accessible the CCMT programme is, moreover, is it is critical to determine the level of quality and the extent in which patients are satisfied with service provided. The study investigated and described the experiences of patients on the Comprehensive HIV and AIDS Care Management and Treatment (CCMT) programme. Purpose The purpose of the research was addressed within a quantitative approach applying descriptive designs. A self-administered questionnaire was used to collect the data that fit the objectives of the research. In this study the population applied to patients who lives in the vicinity of Tshwane District, Pretoria West and Kalafong Hospitals; Method Systematic random sampling consisted of 402 patients on the CCMT programme in three hospitals namely Tshwane District, Pretoria West and Kalafong Hospitals. Eligible participants were those who were 18 years and older and have been on the CCMT programme for 6 months or longer. Data was captured on Microsoft Excel 2007 and descriptive statistics was analysed with Stata 10. Results In this study 415 interviews were secured in all three hospitals, A total of 415 questionnaires were distributed in all three hospitals where a response of 97% was obtained, which compares favorably with the experience of other researchers. Conclusion The study reveals that the CCMT programme in Tshwane District, Pretoria West, and Kalafong hospitals is being implemented in accordance with what has been prescribed in the operational plan for the comprehensive HIV and AIDS Care, Management and Treatment for South Africa as it is accessible, of good quality with patients that are generally satisfied with service provided. Key terms: HIV and AIDS, health care, accessibility, quality, management, guidelines.
Thesis (MPH)--University of Limpopo, 2009.
Keywords: HIV/AIDS; HIV